If the US-China trade war is here to stay, what are the risks and opportunities for other GVC economies outside the war zone? - Witada Anukoonwattaka; Pedro Romao; Richard S. Lobo (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2021)
Over the last three years, trade tensions between the United States (US) and China have transformed a fairly open bilateral trading environment into a rather protectionist one. The new administration of the United States has maintained most of the bilateral tariffs and non-tariff barriers put in place by the previous administration. Moreover, incentives to diversify trade partners and localisation have been intensified following COVID-19-induced global supply-chain disruptions. Continuing bilateral trade tensions between the world's largest economic powerhouse scan be expected to have significant impacts on the rest of the world. While it is intuitive to conclude that bilateral trade restrictions create new opportunities for others, deep economic interdependence through Global Value Chains (GVCs) complicate matters considerably. Impact assessment needs to consider supply-side relationships between each economy and the two GVC giants. Therefore, in this paper, we develop an analytical framework based on input-output data to assess how existing trade flows will be affected by tariff escalation between the US and China. The aim is to identify potential winners and losers among third-party economies. More specifically, we used product-level data and a new UN-ESCAP WWZ decomposition technique of MRIO trade in value-added data to (1) model tariff's impacts on US-China bilateral trade and then (2) track how third-countries might be impacted via international supply-chains: both negatively, via lower exports in affected (tariffed) links, as well as positively via enhanced exports demand in alternative ones. We find that the current trade war has been overall positive for third-party economies, shifting US 61.1 billion in net exports away from the US-China link towards other economies. Due to export asymmetries in the US-China bilateral trade relationship, opportunities for third-party economies emerge more from the US tariff imposition than a vice versa. Indeed, our model indicates that the supply-side reconfiguration to avoid US tariffs accounted for more than 80% of third-party economies' gains, equivalent to US 49.5 billion in net exports coming from China to the US diverted. Mexico, Canada, Republic of Korea, Germany and Japan are among the top beneficiaries. Ultimately, lingering trade tensions between the world's two largest economies will continue to pressure international trade downwards, while accelerating pre-existing trends, such as diversification of supply chains.
Keywords: C67; F02; F13; 330; global value chains; trade war; protectionism; trade policy; bilateral trade; tariffs